2009
DOI: 10.1074/mcp.m800202-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Replication-competent HSV-1 Cgal+ Strain Signaling Targets in Human Hepatoma Cells by Functional Organelle Proteomics

Abstract: In the present work, we have attempted a comprehensive analysis of cytosolic and microsomal proteomes to elucidate the signaling pathways impaired in human hepatoma (Huh7) cells upon herpes simplex virus type 1 (HSV-1; Cgal ؉ ) infection. Using a combination of differential in-gel electrophoresis and nano liquid chromatography/tandem mass spectrometry, 18 spots corresponding to 16 unique deregulated cellular proteins were unambiguously identified, which were involved in the regulation of essential processes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…Upregulation of PP2A scaffold subunit A and subsequent dephosphorylation of Tyr-307 in the catalytic subunit was found, suggesting PP2A activation in Huh7 infected cells [51,52]. Activation of serine-threonine PP2A was found in Huh7 cells upon HSV-1 infection, and PP2A activation paralleled dephosphorylation and inactivation of the downstream mitogen-activated protein (MAP) kinase pathway [53]. In this study, the up-regulation of PP2A was found in TGEV infected ST cells, suggesting PP2A plays an important role in the dephosphorylation of cellular and viral protein during TGEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of PP2A scaffold subunit A and subsequent dephosphorylation of Tyr-307 in the catalytic subunit was found, suggesting PP2A activation in Huh7 infected cells [51,52]. Activation of serine-threonine PP2A was found in Huh7 cells upon HSV-1 infection, and PP2A activation paralleled dephosphorylation and inactivation of the downstream mitogen-activated protein (MAP) kinase pathway [53]. In this study, the up-regulation of PP2A was found in TGEV infected ST cells, suggesting PP2A plays an important role in the dephosphorylation of cellular and viral protein during TGEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Post-transcriptional regulation, such as alternative splicing, delayed translation, and mRNA degradation, can all affect the protein level that results from a given transcriptional output. While proteomic analyses have not yet been applied to infected neurons, early results from alternative models (Loret et al 2008; Skiba et al 2008; Santamaria et al 2009) suggest that these techniques will likely be fruitful for gaining comprehensive data about proteins levels in infected cells.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, many viruses also induce general changes in the protein composition of infected cells; for example, proteomic changes may occur as a result of the inhibition of cellular macromolecule synthesis or the activation of host antiviral responses. These changes can be monitored by various approaches, including quantitative proteomics, which has been used to characterize changes in the total proteome of CHIKV-infected cells (27) or the nucleolar proteome in coronavirus-or influenza virus-infected avian cells (28,29), to analyze changes in endoplasmic reticulum-mitochondrion contacts induced by human cytomegalovirus infection (30), to elucidate the signaling pathways impaired in human hepatoma cells during herpes simplex virus type 1 infection (31), and to identify host proteins associated with picornavirus RNAs (32). The identification of relocalized host cell components and/or host cell components with altered quantities during infection is especially important for understanding positive-strand RNA viruses.…”
mentioning
confidence: 99%